The Effect of Service Quality, Business Location, Products, and Trust on Customer Satisfaction of Micro-Businesses in the Culinary Sector in Bima City - Nurlaila; muhammad rizkan; syafruddin; Khas Sukma Mulya (CV Edujavare Publishing, 2026)
This study aims to analyze the influence of service quality, business location, product, and trust on customer satisfaction for micro-enterprises in the culinary sector in Bima City. The study employs a quantitative approach using a survey method involving 96 respondents selected through purposive sampling. Data were collected via questionnaires using a Likert scale and analyzed using multiple linear regression with the aid of SPSS. As the residual normality test results did not meet the assumption of normality, parameter significance testing was conducted using the bootstrapping method. The results indicate that, individually, service quality and trust do not have a significant effect on customer satisfaction, whereas business location and product have a positive and significant effect. Simultaneously, service quality, business location, product, and trust significantly influence customer satisfaction (F = 53.788; Sig. < 0.001). The Adjusted R-squared (R²) value of 0.690 indicates that 69% of the variation in customer satisfaction can be explained by the four research variables, while the remaining 31% is influenced by factors outside the research model. These findings suggest that business location and product quality are the dominant factors in enhancing customer satisfaction for culinary micro-enterprises in Bima City.